Teaching corporate crisis management through business ethics education. Issue 5 (2014) - ,
Abstract : Purpose – The purpose of this research was threefold, including to provide a four‐point rationale for teaching corporate crisis management as a module within a course on ethical decision‐making in business and organizations; to provide evaluative data supporting this approach; and to highlight the implications of this approach for human resource development and training.Design/methodology/approach – Thirty‐four undergraduates in a required course on ethical decision‐making in business and organizations completed pre‐ and post‐course assignments assessing their knowledge about crisis/management, as well as their skills in crisis recognition, evaluation and action planning. Participants also completed a survey on their perceptions of the crisis management module and its placement within the ethics course.Findings – Statistical analyses demonstrated significant knowledge acquisition on crisis/management; significant skill development on crisis recognition, evaluation and action planning; and significantly greater "true positives" and significantly fewer "false negatives" in post‐course identification of crisis warning signs. Perceptions of the crisis management module and its placement within the course on ethical decision‐making were positive.Research limitations/implications – Although the sample size was relatively small, small samples are associated with a greater risk of failing to detect an effect that is present, rather than the greater predicament of erroneously concluding that an absent effect is actually present. This information, coupled with the fact that the results demonstrated not only statistical significance but also large effect sizes using Cohen's d, inspires confidence. Nonetheless, additional assessment with larger samples would allow for the possibility of convergent evidence. Similarly, additional assessment within different organizational contexts, including applications in human resource training and development is warranted. Future research should also include assessment of specific underlying teaching strategies and evaluation of whether certain models are associated with greater learning on a broader range of crisis management skills.Practical implications – Programs in business ethics education and training comprise one useful context in which to teach corporate crisis management. The program specified here addresses two training needs previously specified in the human resource development (HRD) literature on crisis management, including identifying specific methods of enhancing recognition or detection of crisis warning signs and also of providing tools and enhancing skills for assessing and containing crisis.Originality/value – Despite the centrality of both ethics and HRD to crisis management, there has been a dearth of research on whether ethics education is a useful context through which to teach this topic. This research addresses this dearth and suggests new avenues for HRD in this respect. Acknowledgements : This research was supported by the Social Sciences and Humanities Research Council of Canada Grant. The author thanks Wanlin Li and Kimberly Heaslip for their assistance with data coding and entry.